Propolis as an Anti-allergy Based on Decrease in Total Eosinophil Count in Rat Models - Rashmika Nambiar; Enny Rohmawaty; Leni Lismayanti (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Propolis is a natural herb derived from plant resins by bees. Propolis contains flavonoids that act as anti-allergy. The composition of flavonoids in propolis varies according to each region like Brazilian, Chinese, Malaysian and Indonesian propolis due to differences in medicinal plants in that area. The aim of this study is to determine the effect of propolis as an anti-allergy and to determine which is the most effective among propolis of Brazilian, Malaysian and Indonesian origin.Methods: An experimental study was performed on 28 Wistar male rats divided into four groups, Brazilian, Malaysian, Indonesian propolis and a negative control group. The used parameter was decreased in total eosinophil count in ovalbumin induced allergy in rats. Propolis or aquadest as control were given orally 0.25ml once daily.Results: All three groups of propolis showed statistically significant results (p<0.05), in decreasing eosinophil count. However, Malaysian and Brazilian propolis showed much more significant effects compared to that of Indonesian propolis. This could be due to the difference in composition and concentration of flavonoids in Indonesian propolis compared to the Brazilian and Malaysian propolis.Conclusion: Propolis has a significant effect as an anti-allergy. Malaysian and Brazilian propolis are more effective as an anti-allergy compare to Indonesian propolis. Propolis can thus be used as an alternative treatment for allergy. [AMJ.2015;2(1):208–12]